An Anesthesia Information Management System (AIMS) as a Tool for Controlling Resource Management of Operating Rooms - Junger, A.; Benson, M.; Quinzio, L.; Michel, A.; Sciuk, G.; Brammen, D.; Marquardt, K.; Hempelmann, G. (Methods of Information in Medicine, 2002)
Objectives: In our department, we have been using an Anesthesia Information Management System (AIMS) for five years. In this study, we tested to what extent data extracted from the AIMS could be suitable for the supervision and time-management of operating rooms.Methods: From 1995 to 1999, all relevant data from 103,264 anesthetic procedures were routinely recorded online with the automatic anesthesia record keeping system NarkoData. The program is designed to record patient related time data, such as the beginning of anesthesia or surgical procedure, on a graphical anesthesia record sheet. The total number of minutes of surgery and anesthesia for each surgical subspecialty per hour/day and day of the year was calculated for each of the more than 40 ORs, amounting to a total of 112 workstations.Results: It was possible to analyze the usage and the utilization of ORs at the hospital for each day of the year since 1997. In addition, annual and monthly evaluations are made available. It is possible to scrutinize data of OR usage from different points of view: queries on the usage of an individual OR, the usage of ORs on certain days or the usage of ORs by a certain surgical subspecialty may be formulated. These data has been used repeatedly in our hospital for decision making in OR management and planning. Conclusions: In assessing the results of our study, it should be considered that the system used is not a specialized OR management tool. Despite these restrictions, the system contains data which can be used for an exact and relevant presentation of OR utilization
Keywords: Financial management; hospital; medical records systems; computerized; operating room information systems; operating room